2004
DOI: 10.1162/089976604322860677
|View full text |Cite
|
Sign up to set email alerts
|

Estimating the Entropy Rate of Spike Trains via Lempel-Ziv Complexity

Abstract: Normalized Lempel-Ziv complexity, which measures the generation rate of new patterns along a digital sequence, is closely related to such important source properties as entropy and compression ratio, but, in contrast to these, it is a property of individual sequences. In this article, we propose to exploit this concept to estimate (or, at least, to bound from below) the entropy of neural discharges (spike trains). The main advantages of this method include fast convergence of the estimator (as supported by num… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
148
0

Year Published

2006
2006
2016
2016

Publication Types

Select...
3
3

Relationship

0
6

Authors

Journals

citations
Cited by 148 publications
(154 citation statements)
references
References 15 publications
6
148
0
Order By: Relevance
“…Given that no specific visual stimuli were presented, we may assume that the spike trains are locally stationary, allowing us to estimate those parameters by means of 5-s long, sliding windows. The estimation of the necessary information and entropy rates was obtained by means of the normalized Lempel-Ziv complexity, a technique that the authors have studied in previous works; see, e.g., Szczepanski et al (2003), Amigó et al (2004). The encoding parameters and window length were chosen precisely on the grounds of our experience with this estimator.…”
Section: Discussionmentioning
confidence: 99%
See 4 more Smart Citations
“…Given that no specific visual stimuli were presented, we may assume that the spike trains are locally stationary, allowing us to estimate those parameters by means of 5-s long, sliding windows. The estimation of the necessary information and entropy rates was obtained by means of the normalized Lempel-Ziv complexity, a technique that the authors have studied in previous works; see, e.g., Szczepanski et al (2003), Amigó et al (2004). The encoding parameters and window length were chosen precisely on the grounds of our experience with this estimator.…”
Section: Discussionmentioning
confidence: 99%
“…This is an alternative to the analysis based on firing rate methods. It was shown that Lempel-Ziv complexity as defined in Lempel and Ziv (1976) can be used successfully as such an estimator (Amigó et al 2004).…”
Section: The Entropy Rate and The Lempel-ziv Estimatormentioning
confidence: 99%
See 3 more Smart Citations